Health and work ability in nurses working in shifts - Fernandes, Adília (2014)
Nurses belong to an occupational category which work processes exhausting both physically and mentally that can change the ability to work and contribute to sleep disturbances, psychological, cardiac and digestive as well as family and social changes. Objectives: Assess the ability to work in nurses working in shifts; check whether nurses who reported higher prevalence of diseases had lower capacity to work, sleep disorders, chronic fatigue, personality changes, interference in social life, domestic and non-domestic activities, cardiovascular symptoms and changes in health in general. Methods: This is a quantitative descriptive and explanatory cross-correlated study. We used the questionnaire “Work Ability Índex” to determine the work ability, to determine the consequences of shift work used the Portuguese version of “Survey of Shiftworkers”. We resorted to a non-probability convenience sample of 343 nurses to perform duties on health units in Nordeste Transmontano region. Results: The sample is composed of 287 female and 56 male. The minimum age of respondents is 22 years and maximum is 61, the average age is 36.73 ± 8.54 years. Determined the work ability, we found that 84.3% of respondents have good (42.3%) or excellent capacity (42%). On average, when increasing the number of injuries/illnesses decreases the work capacity (p = 0.000), increase: sleep disturbance (p = 0.038); chronic fatigue (p = 0.000); personality changes (p = 0.000); interference in social (p = 0.014) and domestic life (p = 0.011); cardiovascular symptoms (p = 0.000) and worsening general health (p = 0.001). Conclusions: The results of this study reinforce the importance to implement surveillance and health promotion programs in order to reduce or avoid the harmful consequences of shift work.